2012
DOI: 10.1002/jbt.21410
|View full text |Cite
|
Sign up to set email alerts
|

Iron overload potentiates diet‐induced hypercholesterolemia and reduces liver ppar‐α expression in hamsters

Abstract: Iron stores and lipids are related to the development of cardiovascular disease. Given that peroxisome proliferator-activated receptor alpha (PPAR-α) regulates important physiological processes that impact lipid and glucose homeostasis, we decided to investigate the effects of iron overload on serum lipids and the liver expression of PPAR-α, 3-hydroxy-3-methylglutaryl coenzyme A reductase, and cholesterol 7α-hydroxylase. Hamsters were divided into four groups. The standard group (S) was fed the AIN-93M diet, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Iron dextran decreased pparα expression, suggesting that it would decrease FA oxidation, thus increasing serum triacylglycerol concentration. Bonomo et al [ 7 ] showed similar effect of iron on the expression of PPAR alpha in hypercholesterolemic hamsters; however this study did not evaluate triacylglycerol metabolism. Oxidative stress and inflammation modulate PPAR receptors in diabetes [ 13 ], suggesting that increased oxidative stress promoted by iron dextran may have resulted in the decreased pparα expression, this was also correlated in this study.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Iron dextran decreased pparα expression, suggesting that it would decrease FA oxidation, thus increasing serum triacylglycerol concentration. Bonomo et al [ 7 ] showed similar effect of iron on the expression of PPAR alpha in hypercholesterolemic hamsters; however this study did not evaluate triacylglycerol metabolism. Oxidative stress and inflammation modulate PPAR receptors in diabetes [ 13 ], suggesting that increased oxidative stress promoted by iron dextran may have resulted in the decreased pparα expression, this was also correlated in this study.…”
Section: Discussionmentioning
confidence: 88%
“…The generation of free radicals might be involved in dyslipidemia and consequently in the pathogenesis of hepatic steatosis [ 3 ] and cardiovascular disease [ 4 ]. Previous data suggests a link between lipids and iron metabolism and that this relationship is influenced by oxidative stress [ 5 7 ]. However, despite a considerable amount of data indicating an increase of both O 2 − and iron content in tissue leads to increased OH − formation, the mechanism of involvement and the role of iron in early stage dyslipidemia remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Silva et al () showed that intraperitoneal injection of iron dextran could decrease fatty acid oxidation in the liver of rats by the inhibition of PPARα and its target genes. In addition, Bonomo et al () showed a similar effect of intraperitoneal injection of iron dextran on the expression of PPARα in hypercholesterolemic hamsters. It is well known that heme iron is better absorbed than non‐heme iron (Seligman et al .…”
Section: Discussionmentioning
confidence: 85%
“…Some animal and epidemiological studies have suggested that high iron levels may have a harmful impact on glucose and lipid metabolism [154][155][156]. It is noteworthy that iron overload attenuates the hepatic expression of Ppar-α, which is an important transcriptional factor that promotes lipid and lipoprotein metabolism [113]. Bonomo et al [113] reported evidence that iron is involved in the pathogenesis of non-alcoholic steatohepatitis (NASH).…”
Section: Ironmentioning
confidence: 99%
“…It is noteworthy that iron overload attenuates the hepatic expression of Ppar-α, which is an important transcriptional factor that promotes lipid and lipoprotein metabolism [113]. Bonomo et al [113] reported evidence that iron is involved in the pathogenesis of non-alcoholic steatohepatitis (NASH). Their data showed that intraperitoneal injection of iron dextran, when associated with a high-fat diet (HFD), caused increased serum cholesterol levels due to a reduction in Ppar-α mRNA expression in the liver tissue of hamsters.…”
Section: Ironmentioning
confidence: 99%